Assessing the relevance of indicators in tracking social determinants and progress toward equitable population health in Brazil - Davide Rasella; Daiane Borges Machado; Marcelo Eduardo Pfeirrer Castellanos; Jairnilson Paim; Celia Landmann Szwarcwald; Diana Lima; Laio Magno; Leo Pedrana; Maria Guadalupe Medina; Gerson Oliveira Penna; Mauricio Lima Barreto (Taylor & Francis Group, 2016)
Background: The importance of the social determinants of health (SDH) and barriers to the access and utilization of healthcare have been widely recognized but not previously studied in the context of universal healthcare coverage (UHC) in Brazil and other developing countries. Objective: To evaluate a set of proposed indicators of SDH and barriers to the access and utilization of healthcare - proposed by the SDH unit of the World Health Organization - with respect to their relevance in tracking progress in moving toward equitable population health and UHC in Brazil. Design: This study had a mixed methodology, combining a quantitative analysis of secondary data from governmental sources with a qualitative study comprising two focus group discussions and six key informant interviews. The set of indicators tested covered a broad range of dimensions classified by three different domains: environment quality; accountability and inclusion; and livelihood and skills. Indicators were stratified according to income quintiles, urbanization, race, and geographical region. Results: Overall, the indicators were adequate for tracking progress in terms of the SDH, equity, gender, and human rights in Brazil. Stratifications showed inequalities. The qualitative analysis revealed that many of the indicators were well known and already used by policymakers and health sector managers, whereas others were considered less useful in the Brazilian context. Conclusions: Monitoring and evaluation practices have been developed in Brazil, and the set of indicators assessed in this study could further improve these practices, especially from a health equity perspective. Socioeconomic inequalities have been reduced in Brazil in the last decade, but there is still much work to be done in relation to addressing the SDH.